2012
DOI: 10.4103/2278-960x.104296
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the cervix in unscreened West African women

Abstract: Background: Cancer of the cervix remains an important health problem amongst women worldwide. Widespread comprehensive cervical cancer control programs have resulted in a marked reduction in the incidence and mortality in most developed countries. Developing countries bear over 80% of the global burden, with only 5% of the global resources for the control of cancer. Majority of the cases in these countries present late and are incurable at the time of diagnosis. Aim: To review the presentation and histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…(19) Again, the larger the family size of residentCSWs, the more tendency to having different social characters in the family. Our study, however, is in agreement with Gaya et al (20) where poverty as a result of large family sizes has been linked to prostitution and could serve as reservoirs for diseases that may lead to cervical lesion. We also observed that the Oredo LGA in Benin City, Nigeria had the highest influx of both migrant 27/89 (30.3%) and teenage 13/ 34 (38.2%) resident CSWs (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…(19) Again, the larger the family size of residentCSWs, the more tendency to having different social characters in the family. Our study, however, is in agreement with Gaya et al (20) where poverty as a result of large family sizes has been linked to prostitution and could serve as reservoirs for diseases that may lead to cervical lesion. We also observed that the Oredo LGA in Benin City, Nigeria had the highest influx of both migrant 27/89 (30.3%) and teenage 13/ 34 (38.2%) resident CSWs (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…The studies of Juneja et al, [14] Shields et al [15] also pointed out these risk factors. [5] Shanta et al in 2000 studied etiologic association and possible risk factors for cervical carcinoma. Sexual and reproductive factors, socio-economic factors (education and income), viruses e.g., herpes simplex virus, HPV, human immunodeficiency virus in cervical carcinogenesis and other factors such as smoking, diet, oral contraceptives, hormones play a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Low socio-economic status, multiple pregnancies, poor sexual hygiene and early marriage are closely related to the population living in rural areas and all of these are important risk factors of cancer cervix. [4][5][6] Cervical cancer is a preventable disease with treatment of precancerous lesions and is also curable at early stages. [7,8] Cervical cytology and human papillomavirus (HPV) co-test are recommended by American College of Obstetricians and Gynecologists as effective screening programs for cancer cervix, but these are not very effective in developing countries like India, where resources are limited and incidence of cervicitis is high.…”
Section: Introductionmentioning
confidence: 99%
“…This finding correlates with findings elsewhere in which squamous cell carcinoma is the most common cancer of the cervix. Gaya et al also encountered maximum cases of squamous cell carcinoma in their studies 14 . This finding is explainable as squamous cell carcinoma accounts for the vast majority of cervical malignancies in sub Saharan Africa with the etiological agent being oncogenic HPV serotypes 15 .…”
Section: Discussionmentioning
confidence: 95%